Biocontrol of root knot nematodes by endophytic fungus isolated from garlic - Khan, Aimal; Hussain, Anwar; Ali, Farman; Hamayun, Muhammad; Iqbal, Amjad; Elansary, Hosam O.; Kim, Ho-youn (Elsevier BV, 2024)
Because of the endophytic fungi's ability to improve host plant fitness and boost their defense they have been used as to control root knot nematode (RKN) infection. RKNs induce root galls by altering growth pattern in the cell elongation zone, thereby obstructing nutrient transport to various parts of the plant. This project was designed to control RKN infestation in Solanum melongena by utilizing plant-friendly endophytic fungi. Garlic plants were used to isolate endophytic fungi which were then screened for their potential to inhibit RKN in S. melongena. Based on its namatocidal potential, the endophyte strain, named GR was selected and identified to be Aspergillus fumigatus with the help of the internal transcribed spacer (ITS) segment of the rRNA genes. The fungus had the ability to release indole acetic acid (IAA), salicylic acid (SA), phenols and flavonoids. The potential endophytes were assessed for the biocontrol of RKN in S. melongena seedlings grown in pots. The isolated strain conferred resistance to RKN penetration, leading to a substantial reduction in the frequency of root galls by 6.8-fold than the control. In comparison to control, endophyte-associated seedlings exhibited a 50 % increase in SA levels, indicating a SA-dependent defense against RKN. The activity of catalase and ascorbic acid was also boosted to suppress ROS generated in the RKN infested seedlings. The culture of the endophytic isolate contained nematicidal phenol (p-hydroxybenzoic acid, caffeic acid, Calycosin) and an alkaloid (Cyclopenin). These findings suggest that the isolated endophyte confers resistance to RKN in Solanum melongena by modulating host physiology and releasing nematicidal substances.